Russia's Border Wars and Frozen Conflicts - Coyle, James J. (Springer International Publishing, 2018)
This book examines the origins and execution of Russian military and political activities in Moldova, Georgia, Ukraine, and Azerbaijan. Using a realist perspective, the author concludes that there are substantial similarities in the four case studies: Russian support for minority separatist movements, conflict, Russian intervention as peacekeepers, Russian control over the diplomatic process to prevent resolution of the conflict, and a perpetuation of Russian presence in the area. The author places the conflicts in the context of international law and nationalism theory.